Health psychology and climate change: time to address humanity’s most existential crisis - Papies, Esther; Nielsen, Kristian Steensen; Araújo-Soares, Vera (Health psychology review, 2024)
Climate change is an ongoing and escalating health emergency. It threatens the health and wellbeing of billions of people, through extreme weather events, displacement, food insecurity, pathogenic diseases, societal destabilisation, and armed conflict. Climate change dwarfs all other challenges studied by health psychologists. The greenhouse gas emissions driving climate change disproportionately originate from the actions of wealthy populations in the Global North and are tied to excessive energy use and overconsumption driven by the pursuit of economic growth. Addressing this crisis requires significant societal transformations and individual behaviour change. Most of these changes will benefit not only the stability of the climate but will yield significant public health co-benefits. Because of their unique expertise and skills, health psychologists are urgently needed in crafting climate change mitigation responses. We propose specific ways in which health psychologists at all career stages can contribute, within the spheres of research, teaching, and policy making, and within organisations and as private citizens. As health psychologists, we cannot sit back and leave climate change to climate scientists. Climate change is a health emergency that results from human behaviour; hence it is in our power and responsibility to address it.
Gesehen am 17.06.2024